2023
DOI: 10.1002/ohn.612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Association of Obesity and Chronic Rhinosinusitis: A Systematic Review and Meta‐analysis

David Hoying,
Katherine Miller,
Julia Tanzo
et al.

Abstract: ObjectiveThe aim of this Meta‐analysis and systematic review was to perform a comprehensive assessment of the association of chronic rhinosinusitis (CRS) with overweight/obesity, leptin hormone, and its associated metabolic dysregulation.Data SourcesOvid MEDLINE, Embase, Web of Science, and Cochrane Central Register of Controlled Trials, were searched for studies from 1946 to October 2022, using predefined syntax.Review MethodsOutcome data for the meta‐analysis were extracted on odds ratios (OR) of CRS prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…30 While our results, in combination with recent Meta-analyses, indicate an association between obesity and respiratory diseases like asthma and CRS, it appears obesity may not be associated with the development of systemic vasculitis as seen in patients with EGPA. 31,32 Although not a small-vessel vasculitis, previous research has shown giant cell arteritis, a systemic vasculitis, was negatively associated with obesity. For these reasons, it may be possible that obesity does not play a role in the development of the small-vessel vasculitis seen in patients with EGPA, and further research on this topic is needed.…”
Section: Discussionmentioning
confidence: 97%
“…30 While our results, in combination with recent Meta-analyses, indicate an association between obesity and respiratory diseases like asthma and CRS, it appears obesity may not be associated with the development of systemic vasculitis as seen in patients with EGPA. 31,32 Although not a small-vessel vasculitis, previous research has shown giant cell arteritis, a systemic vasculitis, was negatively associated with obesity. For these reasons, it may be possible that obesity does not play a role in the development of the small-vessel vasculitis seen in patients with EGPA, and further research on this topic is needed.…”
Section: Discussionmentioning
confidence: 97%